Bartolomeo Cristofori and the Invention of the Piano - Pollens, Stewart (Cambridge Cambridge University Press, 2017)
This is the first comprehensive study of the life and work of Bartolomeo Cristofori, the Paduan-born harpsichord maker and contemporary of Antonio Stradivari, who is credited with having invented the pianoforte around the year 1700 while working in the Medici court in Florence. Through thorough analysis of documents preserved in the State Archive of Florence, Pollens has reconstructed, in unprecedented technical detail, Cristofori's working life between his arrival in Florence in 1688 and his death in 1732. This book will be of interest to pianists, historians of the piano, musicologists, museum curators and conservators, as well as keyboard instrument makers, restorers, and tuners.
Keywords: 18th Century (1701-1800); 17th Century (1601-1700); Keyboard instrument; Italy